Importance of Selenium in the Environment and Human Health 2020
DOI: 10.5772/intechopen.88960
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in the Prevention and Treatment of Hepatocellular Carcinoma: From Biomedical Investigation to Clinical Application

Abstract: Selenium is a micronutrient that had been suggested to reduce the risk of cancer. Hepatocellular carcinoma (HCC), a prevalent disease and one of the most lethal cancers in the world, awaits new alternative treatment strategies to improve patients' survival. As an essential trace element, selenium has been studied for its anticancer properties in both oxidative stress and inflammatory-related mechanisms that may contribute to HCC growth and metastasis. In recent decades, increasing studies have investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Other contrasting data were reported on selenium dependent GPx. Se deficiency increases cancer incidence [311]. Hence, low Se levels have been observed in HCC patients' blood, while its supplementation decreased the risk of cancer [311].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other contrasting data were reported on selenium dependent GPx. Se deficiency increases cancer incidence [311]. Hence, low Se levels have been observed in HCC patients' blood, while its supplementation decreased the risk of cancer [311].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Se deficiency increases cancer incidence [311]. Hence, low Se levels have been observed in HCC patients' blood, while its supplementation decreased the risk of cancer [311]. However, the seleno-protein GPx2 plays an important role in the progression of malignant tumors [312].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…The use of Selenaza drug in the postoperative period promoted earlier recovery of the detoxification and synthetic function of the liver in patients with liver tumors [1]. The protective effect of selenium-containing drugs in liver diseases is determined by transformation of toxins into inactive forms in its environment, preservation of the hepatocyte membranes structure as a result of stimulation of glutathione peroxidases reducing the level of free radicals and LPO, acceleration of ethanol catabolism, and the effect on both humoral and cellular immunity [10]. Selenium is also essential for the synthesis of liver enzymes [11].…”
Section: Resultsmentioning
confidence: 99%
“…This study proved the protective effect of curcumin and selenium, alone and in combination with each other, this finding in agreement with previous studies where curcumin showed multiple pharmacological activities, including anti‐inflammation and antioxidant (Xie et al, 2020), and have an essential role in inhibiting the progression of HCC through various pathways (Tan & Norhaizan, 2019; Zhang et al., 2018). Previous studies have shown a potential inverse relationship between selenium levels and the occurrence of HCC (Cheng et al., 2019).…”
Section: Discussionmentioning
confidence: 98%